Protease from Mucor subtilissimus UCP 1262: Evaluation of several specific protease activities and purification of a fibrinolytic enzyme - NASCIMENTO,THIAGO P. (2020)
Abstract The industrial demand for proteolytic enzymes is stimulating the search for new enzyme sources. Fungal enzymes are preferred over bacterial enzymes, and more effective and easier to extract. The aim of this work was to evaluate the potential of protease production by solid state fermentation (SSF) of Mucor subtilissimus UCP 1262, evaluate different specific activities, purify and partially characterize the enzyme in terms of biochemical as to the optimal pH and temperature. Initially, the enzyme crude extract was screened for 3 different proteolytic activities, collagenolytic (161.4 U/mL), keratinolytic (39.6 U/mL) and fibrinolytic (26.1 U/mL) in addition to conventional proteinase activity. After ammonium sulfate precipitation, the active fractions with fibrinolytic activity were dialyzed in 15 mM Tris-HCl buffer, pH 8, loaded onto DEAE-Sephadex A50 ion-exchange column and gel filtrated through Superdex 75 HR10/300. The enzyme showed a fibrinolytic maximum activity at 40 C and pH 9,0. The purified enzyme showed activity against a chromogenic chymotrypsin substrate, SDS-PAGE showing a molecular mass of approximately 70 kDa and, the specific activity of 25.93 U/mg. These characteristics suggest that the enzyme could be and efficiently produced in a simple and low-cost way using Mucor subtilissimus UCP 1262 in SSF.